An Experimental Study of Ethanolic Extract of Myristica fragrans in Morphine Dependence - Zaheer, Imran; Rahman, Syed Ziaur; Khan, Rahat Ali; Parveen, Mehtab (Bangladesh Journal of Medical Science, 2016)
Objective: To evaluate the role of ethanolic extract of Myristica fragrans in morphine dependence. Methods: Wistar albino rats were made moderate and severe grade morphine dependence by administering morphine sulphate in dose of 10 mg /kg (i.p.), twice daily for 4 days and by increasing doses of 10-100 mg/kg (i.p.), twice daily for 7 days, respectively. The signs of spontaneous abstinence syndrome were recorded 12 hours in both studies after the last dose of morphine for 30 minutes and quantified by counted and checked signs. Ethanolic extract of Myristica fragrans (EEMF) was administered p.o. in different regimen: (a) EEMF 200 mg/kg along with morphine twice daily for 4 days and 7 days in moderately and severely induced morphine dependence group, respectively. (b) EEMF 400 mg/kg (p.o.), single dose10 hours after the last dose of morphine in both moderately and severely induced morphine dependence rats. Result: Oral administration of EEMF in both study groups caused significant reduction in the scores of counted and checked signs of morphine abstinence syndrome as compared to active morphine control group. The reduction was significantly more in regimen a as compared to regimen b. Conclusion: Ethanolic extract of Myristica fragrans seed significantly reduced the mean scores of variouscounted signs and checked signs of morphine withdrawal syndrome and might give a solution as a substitute therapy in morphine de-addiction. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.224-229